Two new species of the genus Zaitzevia Champion (Coleoptera: Elmidae) from Guangdong Province, China - Bian, Dong-Ju; Hu, Yu-Qi (Zootaxa, 2024)
Two new species of Zaitzevia Champion, 1923, Zaitzevia acuta sp. nov. and Zaitzevia nanlingensis sp. nov. are described from Guangdong Province, China and photographs of habitus and male aedeagus are provided. This genus is recorded from Guangdong Province for the first time.